La traducción de las Odas de Anacreonte y de Museo de Graciliano Afonso: concepto y métodos. Graciliano Afonso’s translation of Anacreonte’s and Musaeus’Odes: concept and methods - Francisco Salas Salgado (Hermeneus, 2024)
Graciliano Afonso Naranjo, Canarian humanist, and prolific writer, published his first translated work in Puerto Rico in 1838: theOdas de Anacreonte. Los amores de Leandro y Hero, was issued along with Afonso’s own literary workEl beso de Abibina. The Puerto Rican text was later transcribed and included into one of the five manuscript volumes containing his works, currently kept at the Museo Canario de las Palmas de Gran Canaria. This article analyses the theoretical aspects that run through these notes either in a latent or an explicit way. Its aim is to ascertain their relation to Graciliano Afonso’s translations and to the specific context where they emerged to identify and systematize the translation principles inspiring him.